Audit firms’ corporate social responsibility activities and auditor reputation - Gunn, Joshua L.; Li, Chan; Liao, Lin; Yang, Jinxuan; Zhou, Shan (Accounting, Organizations and Society, 2024)
Professional audit firms increasingly engage in Corporate Social Responsibility (CSR) activities. This paper examines the effect of audit firms' CSR activities on auditors’ reputation. We find that audit firms that engage in CSR experience an increase in the size of their client base compared to audit firms that do not engage in CSR. The effect is stronger for audit firms without existing reputation from a Big 4 brand name or industry specialization. We also find that clients that value CSR are more likely to hire audit firms that engage in CSR. Overall, our results suggest that CSR is an effective tool for audit firms to build their reputation in the marketplace.